Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content 1. The actuality of qualitative research and its challenges at Al-Quds University, as perceived by a representative sample of university professors and student researchers Co-Prof. Mohammad Awad Shuibat, Mrs. Natasha Omar Abu Ziyad, Mr. Nayef Abd Alraouf Alkhateeb 2. Employing secondary schools leaders for information and communications technology and its effect on organizational culture in Al-Medina Mrs. Omneyah Abdullah Abutarboush 3. Education and economic growth in Kingdom of Saudi Arabia during the period from 2000AD to 2020 AD Mrs. Wafaa Mohamad Al-Otaibi 4. The role of the Palestinian Ministry of Education in influencing Palestinian students’ attitudes toward vocational and technical education from experts’ perspective Mr. Amjad Ziad Hassan Sheikh Ali 5. The effectiveness of an enrichment teaching program based on STEM approach in developing the 21st skills of intermediates school students Dr. Nasser Mohammed Almutairi 6. Mindfulness and its relationship to the quality of academic life in the light of distance education on a sample of master’s students at Taif University Mrs. Esraa Saad Alomari, Dr. Azza Mohammed Abdu Hella